Rancang Bangun Sistem Anjungan Layanan Mandiri Pencetakan Dokumen - Alri, Hamid; Sambul, Alwin M.; Sompie, Sherwin R.U.A (Universitas Sam Ratulangi, 2021)
Document printing self-service platform is a printing machine that uses a computerized system to serve and assist users in printing documents, for example for the needs of legalizing academic documents such as diplomas needed by alumni who want to find work or continue their education to a higher level as evidence and complementary documents. However, the process of managing document legalization is still done manually. alumni come with a copy of the document and bring proof of payment then submit it to the officer in charge of legalizing the document in the validation process and doing data collection manually. This allows the legalization process activities to not be carried out properly which results in documents being scattered or lost and there is no certainty that the document legalization process will be completed.Â The research entitled